PENGARUH LATIHAN PUSH OFF TERHADAP DAYA LEDAK OTOT TUNGKAI PESILAT TUAH PANDEKA RAJO KEC. AMPEK ANGKEK CANDUNG KAB. AGAM - Rahmadani Rahmadani; Gusril Gusril (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2018)
The problem in this study is the low explosive ability of the leg muscles of the Tuah Pandeka Rajo. The purpose of this study was to see the effect of Push Off training on the explosive power of the leg muscles of the Tuah Pandeka Rajo. This research is a quasi experiment. The population in this study was pesilat Tuah Pandeka Rajo. Sampling is done by